Somatostatin receptor scintigraphy in advanced renal cell carcinoma - Freudenberg, L. S.; Gauler, T.; Görges, R.; Bauer, S.; Stergar, H.; Antoch, G.; Bockisch, A.; Schütte, J. (Nuklearmedizin - NuclearMedicine, 2008)
Aims: Objective of this prospective study was to evaluate the role of somatostatin receptor scintigraphy (SRS) in advanced renal cell carcinoma (RCC) with respect to potential therapy with somatostatin analogue (SST-A) and to assess the response rate under therapy with SST-A. Patients, methods: 16 patients with documented progression of histologically confirmed advanced RCC were included. Planar whole-body SRS was performed 4, 24 and 48h post i.v. injection of 175–200 MBq 111In-pentetreoide. 5 and 25 h p.i. SPECT of thorax and abdomen were performed. Documentation of somatostatin receptor expression via SRS in >50% of known tumour lesions was the criteria for treatment start with SST-A (Sandostatin LAR®-Depot 30mg i.m. every four weeks). Results: In 9/16 of the patients SRS showed at least one metastasis with moderate (n = 5) or intense (n = 4) tracer uptake. Lesion-based SRS evaluation showed only 12.1% (20/165) of all metastases. Most false-negative lesions were located in the lungs. In two patients, the majority of the known metastases was SRS positive and these patients received SST-A therapy. The first radiographic evaluation after a twomonth interval showed progressive disease in both patients. Conclusions: We conclude that SRS is of limited value in staging of advanced RCC. In our patients SST-A did not result in a growth control of RCC. Consequently, the use of SST-A in advanced RCC seems to be no relevant therapeutic option.
Keywords: Somatostatin receptor scintigraphy; renal cell carcinoma; somatostatin analogue; phase-II-trial